Medical cannabis: Mechanisms of action and therapeutic targets - Kowalczyk, Klaudia; Lasek, Patryk; Trąbka, Natalia; Binkowska, Paulina; Demidowicz, Gabriela; Lasota, Nina; Smerdzyński, Maciej; Łach, Katarzyna; Ściurka, Kinga; Panuciak, Kinga (Journal of Education, Health and Sport, 2024)
Introduction: In recent years, multiple publications underscored many beneficial properties associated with medical marihuana. Its current applications encompass pain relief, multiple sclerosis, the treatment of anxiety disorders, Dravet syndrome and other. It can potentially extent to the treatment of patients with fibromyalgia or in people with diabetic complications. The expansive potential of medical cannabis in the prevention and treatment of many diseases is seen in its complex and multidirectional mechanisms of action. Medical marihuana has impact on cannabinoid receptors, and it exerts effects through many other molecular targets. Aim of the study: This review seeks present mechanisms of action of medical marihuana and explore its potential therapeutic targets. Materials and methods: A comprehensive review of literature available in the PubMed and Google Scholar databases was performed, using the following keywords: "medical marihuana", "medical cannabis", "medical marihuana mechanism of action", "therapeutic targets of medical marihuana", "endocannabinoid system", “medical marihuana in pain treatment”, “medical marihuana amygdala body”, “medical marihuana serotonin receptors”. Conclusions: Medical marihuana emerges as a promising candidate in the treatment of many diseases and common condition. However, further research is imperative to ascertain the effects of the drug and transform it into an effective medication which maximizes benefits and minimalizes side effects.